Dilemma of Democracy: Reasons for the Failure of Democracy in Pakistan - Khalid, Talha; Usman Askari, Muhammad (Annals of Human and Social Sciences, 2023)
This article presents critical analysis of the dilemma of democracy in Pakistan. The objective of this study was to find out the major reasons behind the failure of democracy in Pakistan as most of the population is confused about what the actual cause is behind it. The design of the study was descriptive and teachers and students of international relation of university of central Punjab were the population of this study. The sample of study was selected through random sampling technique. In order to collect data, a validated questionnaire was used by the researcher. The major findings of the research showed that most of the population presented illiteracy, corruption, unfair justice system, pressure groups, feudal and tribal system as the major reasons for the failure of democracy in Pakistan and suggested technocratic system and presidential system as the major solution for the disoriented situation in the country. On the basis of research, a major recommendation of a technocratic system was provided by the researcher.